The Impact of War on Vietnamese in Robert OlenButler short story "Open Arms" - Kerboul, Marwa; Lazim, Sana (Al-Adab Journal, 2025)
The Impact of War on Vietnamese in Robert OlenButler short story "Open Arms"’Marwa Hadi Kerboulmarwa.hadi2103m@coeduw.uobaghdad.edu.iqDr. Sana Hassan Lazimsanalazim@coart.uobaghdad.edu.iqDepartment of English Language, College of Education for women, University of Baghdad Abstract: Since the dawn of humanity violence caused by war or armed conflicts between nations or within the same nation are marked with Trauma and those individuals who face these traumatic events suffer for the rest of their lives and rarely survive its nightmarish shadow. Trauma is a Greek word means wound, however its meaning started to refer to spiritual rather than physical injuries. During the Eighteenth Century it is used to refer to emotional and psychological scars left by violent or upsetting experiences. This study refers to Trauma theory that is explained and developed by Cathy Caruth. This epistemological and ethical perspective is laid forth in her highly significant work. Depending on the theory of Trauma, the analysis will examine the impact of the war on Vietnamese immigrants to the United States and the hardships they faced, which led them to develop mental illnesses such as identity disorder, isolation, self-torture rejection, and difficulties of adaptation and loss of self-esteem.The study presents Trauma theory; its evolution, pioneers, uses, significance, and concepts. It also sheds light on the works and life of Robert Olen Butler, an American writer who served as an interpreter and an unofficial student of Vietnamese culture during the Vietnam War after briefly working in counterintelligence. It presents the short story of Open Arms. The story introduces Thap, who appears to be a devoted communist and is a North Vietnamese. Because his family was slain by the communist party, he plots with the Australians. His traumatic experience led him to committed suicide.